Investigation of the Large-Scale Pallet by Recycled Polypropylene and the Sequential Valve Gate System during the Injection Molding - Chun-Der Cheng; Hsi-Hsun Tsai; Yi-Ling Liao (Advances in Polymer Technology)
Plastic pallets are essential devices for the transport of industrial products within containers and can be made from recycled plastics to be more environmentally friendly. However, numerous thin reinforcing ribs are required to mold such large-size pallets, thereby requiring a large-scale injection-molding machine. Many filling gates can reduce the welding lines to enhance the structural strength of the pallet to achieve injection molding using a lower locking force machine. This study simulated the production of recycled polypropylene plastic pellets using a 3500-ton super-large injection-molding machine and the Moldex3D package to derive the flow analysis of the moldability. The PTC Creo software is used to construct plastic pallets (1100 mm×1100 mm×140 mm), filled by twelve gates using a baffle cooling system. During the four-stage filling of the sequential valve gate system, the flow front spreads from the central gate to the four corners of the pallet, decreasing the number of welding lines, with an average filling pressure of 19.23 MPa by a sequential valve gate scheme which is approximately 65% of the concurrent valve gate opening scheme. The maximum clamping force by this sequential valve gate opening scheme in the molding of plastic pallet is 874.6 tons, only half of the one by concurrent valve gate opening scheme. The average welding angle was 85.7° in the concurrent valve gate opening scheme, with smaller angles than that of the sequential gates controlled scheme. The maximum temperatures during the filling by the two schemes with the concurrent valve gates opened and the sequential gates controlled were 230.5 and 232.5°C, respectively. The sequential valve gate opening scheme’s warpages are smaller than the ones by the concurrent valve gate opening scheme. The warpages of the pallet by the sequential valve gate system are smaller than the ones by the concurrent valve gate system. A higher temperature of the cooling channel and a medium level of cooling time result in lower warpage of the pallet.